2018
DOI: 10.1111/ics.12442
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sensitive skin barrier function: basic indicators and sebum composition

Abstract: Analysis of lipid functions suggested that the main reason for SS development in women might be a barrier dysfunction caused by excessive apoptosis and lack of water. Therefore, anti-allergy additives in cosmetic products that could inhibit apoptosis of keratinocytes and methods to maintain the stability of water molecules in the skin should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…Biao Jiang et al analyzed the lipids on psychological stress‐induced sensitive skin and found that differential lipids were mainly involved in damaging the skin permeability and antimicrobial barrier functions . Fan Linna et al found that sebum secretion in the sensitive skin (SS) group was lower than that in the nonsensitive skin (NS) group, suggesting that the development of SS might be associated with sebum secretion and its specific components . Nojiri H et al found that stimulating the barrier function and improving the ceramide profile could improve the lactic acid sensitivity in sensitive skin .…”
Section: Discussionmentioning
confidence: 99%
“…Biao Jiang et al analyzed the lipids on psychological stress‐induced sensitive skin and found that differential lipids were mainly involved in damaging the skin permeability and antimicrobial barrier functions . Fan Linna et al found that sebum secretion in the sensitive skin (SS) group was lower than that in the nonsensitive skin (NS) group, suggesting that the development of SS might be associated with sebum secretion and its specific components . Nojiri H et al found that stimulating the barrier function and improving the ceramide profile could improve the lactic acid sensitivity in sensitive skin .…”
Section: Discussionmentioning
confidence: 99%
“…After cleaning the face with water and drying gently with paper towels, subjects rested for 30 min in a controlled environment (room temperature at 20–25°C, relative humidity of 50–60%). Afterwards, the following parameters were sequentially measured on the right cheek with the respective device: TEWL values (Tewameter TM 300) first, stratum corneum hydration (SCH) (Corneometer CM 825), sebum content (Sebumeter SM 815), erythema index (Mexameter 18) and skin surface pH values (Skin‐pH‐meter pH 905) . Each measurement was repeated three times, and the average of three readings was taken.…”
Section: Methodsmentioning
confidence: 99%
“…A non-parametric two-independent sample test was used to analyse the significance between groups. ***P < 0.001. values (Skin-pH-meter pH 905) [17,18]. Each measurement was repeated three times, and the average of three readings was taken.…”
Section: Measurement Of Skin Biophysical Propertiesmentioning
confidence: 99%
“…[5] We speculated that the reason for the paradoxical occurrence of disparate TEWL and slightly different pH with almost the same circadian rhythm of SSL excretion content would be alterations in SSL composition. In this study, lipidomics and established methods from our earlier studies [8][9][10][11][12][13] were used to reveal the variations in the SSL profile through a comprehensive analysis in order to understand the paradox of dramatically different TEWL and decreased pH with almost the same circadian rhythm of SSL excretion content.…”
Section: Questions Addressedmentioning
confidence: 99%